Medien als Entwicklungswerkzeuge - Kremer, H.-Hugo (bwp@ Ausgabe13, Selbstorganisiertes Lernen in der beruflichen)

Alphabetisierung und Grundbildung im Kontext des Erwerbs beruflicher Handlungskompetenz - Kremer, H.-Hugo (Innovative Forschung - innovative Praxis in der Alphabetisierung und Grundbildung)

Lehren mit Lernobjekten - Kremer, H.-Hugo; Pferdt, F. G. (Wirtschaft und Erziehung)

An Incremental Approach to the Analysis and Transformation of Workflows Using Region Trees - Hauser, Rainer; Friess, Michael; Kuster, Jochen; Vanhatalo, Jussi (IEEE Transactions on Systems, Man, and Cybernetics, Part C (Applications and Reviews))

Generating Instance Models from Meta Models - Ehrig, Karsten; Küster, Jochen; Taentzer, Gabriele (Software and Systems Modeling)

Unternehmensweit verstehen – unternehmensweit entwickeln: Von der Modellierungssprache zur Softwareentwicklungsmethode - Engels, Gregor; Sauer, Stefan; Soltenborn, Christian (Informatik-Spektrum)
Sollen wir UML 1.4, UML 2.0 oder eine ganz andere Modellierungssprache für unsere Softwareentwicklung einsetzen? Der folgende Beitrag zeigt, dass bei der Festlegung einer unternehmensweiten Entwicklungsmethode nicht die Frage nach der Modellierungssprache im Vordergrund stehen sollte. Viel entscheidender für den Erfolg von Softwareentwicklungsprojekten in einem Unternehmen ist ein einheitliches Verständnis der Entwicklungskonzepte und -artefakte sowie ihrer Beziehungen untereinander. Eine Einigung über ein unternehmensweites Domänenmodell der Softwareentwicklungskonzepte sollte deshalb vor der Auswahl von Modellierungssprachen, eines konkreten Vorgehensmodells und geeigneter Werkzeuge erfolgen.

Formalisierung der funktionalen Anforderungen mit visuellen Kontrakten und deren Einsatz für modellbasiertes Testen - Güldali, Baris; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends)
Wir haben in diesem Beitrag einen Ansatz zur Formalisierung der UML-Anwendungsfallsbeschreibungen vorgestellt, um Anwendungsfälle effektiv für Testzwecke einsetzen zu können. Dabei werden die textuellen Beschreibungen der Vor- und Nachbedingungen mit visuellen Kontrakten formalisiert. Die visuellen Kontrakte beschreiben die Änderungen bezüglich der fachlichen Daten nach der Ausführung des Anwendungsfalls. Mit visuellen Kontrakten können während der Testfallspezifikation Testeingaben generiert und während der Testausführung Testausgaben überprüft werden. Für visuelle Kontrakte wurden Werkzeuge entwickelt, die die Einbindung der visuellen Kontrakte in den Entwicklungs- und Testprozess ermöglichen.

Quasar Enterprise - Engels, Gregor; Voß, Markus (Informatik-Spektrum)
Die Gestaltung und Weiterentwicklung großer Anwendungslandschaften gilt heutzutage als eine der größten Herausforderungen in der Softwaretechnik. Als Lösungsansatz wurde in den letzten Jahren vielfach das Paradigma einer serviceorientierten Architektur (SOA) diskutiert und insbesondere durch herstellerspezifische Technologien unterstützt. Dieser Beitrag widmet sich einer häufig vernachlässigten methodischen Herangehensweise und stellt mit Quasar Enterprise einen strukturierten und in der Praxis erprobten Lösungsansatz vor. Insbesondere werden konkrete Verfahrensbausteine für eine durchgängige Methode vorgestellt, die einem Architekten helfen, eine auf das zu unterstützende Geschäft ausgerichtete Anwendungslandschaft zu entwickeln und zu warten. Wesentliche Charakteristika von Quasar Enterprise sind der konsequente Einsatz einer serviceorientierten Herangehensweise, die Verwendung eines Architektur-Frameworks als Strukturierungsgrundlage und die Aufbereitung der Methode in Form von 20 Verfahrensbausteinen.

Linking Customer Value to Customer Share in Business Relationship - Ulaga, W; Eggert, A (Creating and Managing Superior Customer Value)

Silicon Nanoparticles: Excitonic Fine Structure and Oscillator Strength - Meier, Cedrik; Lüttjohann, Stephan; Offer, Matthias; Wiggers, Hartmut; Lorke, Axel (Advances in Solid State Physics)

Quasar Enterprise: Anwendungslandschaften serviceorientiert gestalten - Engels, Gregor; Hess, Andreas; Humm, Bernhard; Juwig, Oliver; Lohmann, Marc; Richter, Jan-Peter; Voß, Markus; Willkomm, Johannes
IT-Anwendungslandschaften in Unternehmen sind komplexe über Jahre gewachsene Gebilde. Sie architektonisch zu gestalten und nachhaltig zu entwickeln braucht eine eigene Technologie jenseits der klassischen Softwaretechnik. Der Ansatz serviceorientierter Architekturen (SOA) ist ein wichtiges Instrument, reicht aber alleine nicht aus. In Quasar Enterprise haben Experten des Softwareunternehmens sd&m eine durchgängige Architekturmethodik für die serviceorientierte Gestaltung von Anwendungslandschaften zusammengetragen, die Erfahrungen aus Dutzenden von Beratungs-, Integrations- und großen Softwareprojekten widerspiegelt. Das Besondere an Quasar Enterprise ist die Sammlung sehr konkreter Methoden, Regeln, Referenzarchitekturen und Muster für die Gestaltung - ausgehend von der Architektur des Geschäfts, über die logische Strukturierung der IT in Services und Domänen, bis hin zu physischen Komponenten und Schnittstellen inkl. deren Kopplung über technische Integrationsplattformen. Teil I beschreibt ein fiktives, aber realistisches Projekt aus der Sicht eines IT-Architekten. Der Leser schaut ihm bei seiner Arbeit über die Schulter und erlangt dabei ein intuitives Verständnis der Artefakte und Verfahrensbausteine von Quasar Enterprise. Das Vorgehen im Projekt erlebt er dabei beispielhaft. Teil II vertieft das Erlernte systematisch. Die Grundlagen für Anwendungslandschaften und SOA werden eingeführt und dann Schritt für Schritt Begriffe, Zusammenhänge und Vorgehensbausteine erläutert. Die Beziehungen zwischen Architekturentscheidungen und Qualitätszielen werden transparent gemacht und Verweise auf weiterführende Literatur gegeben. Das Buch richtet sich an alle, die etwas über Anwendungslandschaften und SOA in der Praxis wissen wollen. Primäre Zielgruppe sind IT-Architekten, erfahrene Softwareingenieure und Berater.

Open Source Stacks - Christ, Fabian; Sauer, Stefan (Open Source: Kommerzialisierungsmöglichkeiten und Chancen für die Zusammenarbeit von Hochschulen und Unternehmen)

Eintrag "Modellierungssprache" - Engels, Gregor (Enzyklopädie der Wirtschaftsinformatik)

Translating African Traditions and Identities. Black Poetry in Contemporary Britain - Tönnies, Merle (Cultures of Translation)

The Visual Strategies of Nineteenth-Century Melodrama - Tönnies, Merle (Anglistik & Englischunterricht 71)

Kulturelle Bedeutungen und Kontexte der indischen Küche in Großbritannien - Tönnies, Merle (Interkulturelle Mahlzeiten. Kulinarische Begegnungen und Kommunikation in der Literatur)

Probing the band structure of InAs∕GaAs quantum dots by capacitance-voltage and photoluminescence spectroscopy - Lei, W.; Offer, M.; Lorke, A.; Notthoff, C.; Meier, Cedrik; Wibbelhoff, O.; Wieck, A. D. (Applied Physics Letters)

Modellbasierter Komponententest mit visuellen Kontrakten - Ellerweg, Jens; Engels, Gregor; Güldali, Baris (INFORMATIK 2008, Beherrschbare Systeme - dank Informatik, Band 1, Beiträge der 38. Jahrestagung der Gesellschaft für Informatik e.V. (GI))

Modellierung von Variabilität in der Geschäftsanalyse – eine industrielle Fallstudie - von der Maßen, Thomas; Wübbeke, Andreas (Produktlinien im Kontext: Technologie, Prozesse, Business und Organisation (PiK 2008))

A Tool for Process Merging in Business-Driven Development - Küster, Jochen; Gerth, Christian; Förster, Alexander; Engels, Gregor (Proceedings of the Forum at the CAiSE'08 Conference on Advanced Information Systems Engineering)
Business-driven development favors the construction of process models at different abstraction levels and by different people. As a consequence, there is a demand for consolidating different versions of process models by merging them. In this paper, we study a basic scenario, derive requirements and present a prototype for detecting and resolving changes between process models.

UML and IP-XACT for Integrated SPRINT IP Management - Schattkowsky, Tim; Xie, Tao (Proceedings of the 5th International UML for SoC Design Workshop (UML-SoC 2008), Anaheim, CA (USA))

Quantum Hall effect in long and in mobility adjusted GaAs/AlxGa1-xAs samples - Diaconescu, D.; Goldschmidt, A.; Reuter, Dirk; Wieck, A. D. (physica status solidi (b))

Magnetotransport in Gd-implanted wurtzite GaN∕AlxGa1−xN high electron mobility transistor structures - Lo, F.-Y.; Melnikov, A.; Reuter, Dirk; Cordier, Y.; Wieck, A. D. (Applied Physics Letters)

Hysteretic magnetotransport inp-typeAlxGa1−xAsheterostructures with In/Zn/Au Ohmic contacts - Grbić, B.; Leturcq, R.; Ihn, T.; Ensslin, K.; Blatter, G.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Coherent spin dynamics in Permalloy-GaAs hybrids at room temperature - Hohage, P. E.; Nannen, J.; Halm, S.; Bacher, G.; Wahle, M.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Electrical detection of photoinduced spins both at room temperature and in remanence - Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W.; Wende, H.; Petracic, O.; Westerholt, K. (Applied Physics Letters)

Room temperature electrical spin injection in remanence - Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Lo, F.-Y.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Wende, H.; Keune, W.; Petracic, O.; Westerholt, K. (Applied Physics Letters)

Spin Accumulation and Spin Relaxation in a Large Open Quantum Dot - Koop, E. J.; van Wees, B. J.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Physical Review Letters)

Magnetic-barrier-induced conductance fluctuations in quantum wires - Hugger, S.; Xu, Hengyi; Tarasov, A.; Cerchez, M.; Heinzel, T.; Zozoulenko, I. V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Compact cryogenic Kerr microscope for time-resolved studies of electron spin transport in microstructures - Rizo, P. J.; Pugžlys, A.; Liu, J.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H.; van Loosdrecht, P. H. M. (Review of Scientific Instruments)

Observation of excited states in a p-type GaAs quantum dot - Komijani, Y.; Csontos, M.; Ihn, T.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (EPL (Europhysics Letters))

Theoretical and experimental investigations of Coulomb blockade in coupled quantum dot systems - Kaiser, F J; Kohler, S; Hänggi, P; Malecha, M; Ebbecke, J; Wixforth, A; Schumacher, H W; Kästner, B; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Temperature-induced spin-coherence dissipation in quantum dots - Hernandez, F. G. G.; Greilich, A.; Brito, F.; Wiemann, M.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Quantum dot as thermal rectifier - Scheibner, R; König, M; Reuter, Dirk; Wieck, A D; Gould, C; Buhmann, H; Molenkamp, L W (New Journal of Physics)

The active guidance module of a rail-bound vehicle as an application for the dependability oriented design in self-optimizing systems - Sondermann-Wölke, Christoph; Geisler, Jens; Müler, Thomas; Trächtler, Ansgar; Böcker, Joachim (ASME 2008 -- International Design Engineering Technical Conferences & Computers and Information in Engineering Conference (IDETC/CIE))
Integrating dependability in self-optimizing systems is a challenging task. Self-optimizing systems incorporate on the one hand the opportunity to apply novel solutions to complex mechatronic systems, but on the other hand constitute a possible risk because of non-determined behavior. The dependability concept in this paper covers both aspects: Increasing safety with selfoptimization and minimizing the risk of self-optimization. This dependability concept is combined with the self-optimization process of the active guidance module which is currently under development at the Collaborative Research Center 614 at the University of Paderborn.

Tactile tissue characterisation by piezoelectric systems - Stroop, Ralf; Uribe, David Oliva; Martinez, Melisa Orta; Brökelmann, Michael; Hemsel, Tobias; Wallaschek, Jörg (Journal of Electroceramics)
For devices having non-linear contact, load plays a fundamental role. Variations in the characteristics of the load cause change in eigenfrequency and amplitude of the vibration. In most technical applications, this unwanted behaviour is cancelled by the use of control algorithms. However, multiple applications, like bond quality monitoring or chemical and pressure sensors, have found that the load may be characterised by interpreting the change in characteristics of a resonant vibrating device used as a sensor. Surgical resection of tumours is a very difficult task. After localising the tumour by the use of imaging techniques, the resection demands the surgeon to decide where and what to resect based on visual and tactile differentiation of tumour and healthy tissue. Exactness of this process could be enhanced if we can provide the surgeon with a device capable of evaluating mechanical characteristics of the tissue much more accurately than the surgeon himself can do. As the mechanical characteristics of tumour and healthy tissue differ but slightly, the task is to design a system with high sensitivity. Therefore, we have developed a resonant actuator-sensor that allows the differentiation among distinct media that have similar mechanical characteristics to tumour and healthy tissue using a piezoelectric bimorph. The design is based on the detection and evaluation of frequency shift and amplitude variation of the fundamental and higher harmonics using one layer for the resonant excitation of vibration and the other one as the sensing element.
Keywords: Piezo ceramics; Bimorph; Tactile sensor; Tumour tissue

Fundamental experiments as benchmark problems for modeling ultrasonic micro-impact processes - Twiefel, Jens; Potthast, Christian; Mracek, Maik; Hemsel, Tobias; Sattel, Thomas; Wallaschek, Jörg (Journal of Electroceramics)
Many ultrasonic processes are based on the mechanical contact of oscillating parts. Within ultrasonic machining (drilling, milling, grinding) micro impacts lead to abrasion at the processed workpiece and hopefully do not damage the tool. In ultrasonic motors ideally neither part gets worn. Thus the appropriate design of contact partners as well as their kinematics is a substantial task during the development of such devices. A first step to optimize contact mechanics is to understand their behavior and dependencies on parameter variations, such as vibration amplitude and pre-stress of the impacting parts. For a detailed understanding models validated with convincing experimental data from measurements are absolutely essential. This paper focuses on simple vibro-impact experiments which can be used as benchmark data for future models. The setup of the experiment and first experimental investigations are described in detail.
Keywords: Contact measurements; Vibro-impact; Ultrasonic application

Development of a biomedical tissue differentiation system using piezoelectric actuators - Uribe, David Oliva; Stroop, Ralf; Hemsel, Tobias; Wallaschek, Jörg (Frequency Control Symposium, 2008 IEEE International)
In neurosurgery, delineation of tumor boundaries during resection of brain tumors is of substantial relevance. During operation distinction between tumor and healthy tissue rely on the abilities of the surgeon based on visual and tactile differentiation. In this paper a high sensitivity actuator-sensor system using a piezoelectric bimorph is presented. Frequency shift and transfer function of the bimorphpsilas voltages are detected and evaluated. Sensorpsilas sensitivity is evaluated using two frequency controls strategies: A phase-locked loop (PLL) and a self-oscillating circuit. Results of measurements conducted on gel-phantoms are presented and discussed.
Keywords: biomedical measurement; brain; cancer; neurophysiology; phantoms; phase locked loops; piezoelectric actuators; surgery; tactile sensors; transfer functions; tumours; PLL; biomedical tissue differentiation system; brain tumor resection; frequency control; frequency shift; gel-phantom; high sensitivity actuator-sensor system; neurosurgery; phase-locked loop; piezoelectric actuators; piezoelectric bimorph; self-oscillating circuit; sensor sensitivity; tactile differentiation; tactile sensor system; transfer function; tumor boundary; visual differentiation; Biomedical measurements; Circuits; Frequency control; Neoplasms; Neurosurgery; Phase locked loops; Piezoelectric actuators; Surges; Transfer functions; Voltage

Evaluation von Standards und Evaluation für Standards. Zentraler Tagungsband der 15. Hochschultage Berufliche Bildung - Beutner, Marc (Qualität in Schule und Betrieb. Forschungsergebnisse und gute Praxis)

Caselli, D.: Beckett's Dante - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)

The Frontiers of the Sea - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

A Nose By Any Other Name - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

Imitators and optimizers in a changing environment - Hehenkamp, Burkhard; Kaarbøe, Oddvar M. (Journal of Economic Dynamics and Control)

Phonon-assisted tunneling between singlet states in two-electron quantum dot molecules - Grodecka, A.; Machnikowski, P.; Förstner, Jens (Physical Review B)
We study phonon-assisted electron tunneling in semiconductor quantum dot molecules. In particular, singletsinglet relaxation in a two-electron-doped structure is considered. The influence of Coulomb interaction is discussed via comparison with a single-electron system. We find that the relaxation rate reaches similar values in the two cases but the Coulomb interaction shifts the maximum rates toward larger separations between the dots. The difference in electron-phonon interaction between deformation potential and piezoelectric coupling is investigated. We show that the phonon-induced tunneling between two-electron singlet states is a fast process, taking place on the time scales of the order of a few tens of picoseconds.
Keywords: tet_topic_qd

Molecular dynamics simulation of defect formation and precipitation in heavily carbon doped silicon - Zirkelbach, F.; Lindner, Jörg; Nordlund, K.; Stritzker, B. (Materials Science and Engineering: B)
The precipitation process of silicon carbide in heavily carbon doped silicon is not yet fully understood. High resolution transmission electron microscopy observations suggest that in a first step carbon atoms form C Si dumbbells on regular Si lattice sites which agglomerate into large clusters. In a second step, when the cluster size reaches a radius of a fewnm, the high interfacial energy due to the SiC/Si lattice misfit of almost 20% is overcome and the precipitation occurs. By simulation, details of the precipitation process can be obtained on the atomic level. A recently proposed parametrization of a Tersoff-like bond order potential is used to model the system appropriately. Preliminary results gained by molecular dynamics simulations using this potential are presented.

Transition between different coherent light–matter interaction regimes analyzed by phase-resolved pulse propagation - zu Siederdissen, Tilman Höner; Nielsen, Nils C.; Kuhl, Jürgen; Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Khitrova, Galina; Gibbs, Hyatt M.; Koch, Stephan W.; Giessen, Harald (Optics Letters)
We present phase-resolved pulse propagation measurements that allow us to fully describe the transition between several light–matter interaction regimes. The complete range from linear excitation to the breakdown of the photonic bandgap on to self-induced transmission and self-phase modulation is studied on a high-quality multiple-quantum-well Bragg structure. An improved fast-scanning cross-correlation frequency-resolved optical gating setup is applied to retrieve the pulse phase with an excellent signal-tonoise ratio. Calculations using the semiconductor Maxwell–Bloch equations show qualitative agreement with the experimental findings.
Keywords: tet_topic_polariton; tet_topic_qw

Theoretical study of phononassisted singlet-singlet relaxation in two-electron semiconductor quantum dot molecules - Grodecka, Anna; Machnikowski, Paweł; Förstner, Jens (physica status solidi (c))
Phonon-assisted singlet-singlet relaxation in semiconductor quantum dot molecules is studied theoretically. Laterally coupled quantum dot structures doped with two electrons are considered. We take into account interaction with acoustic phonon modes via deformation potential and piezoelectric coupling. We show that piezoelectric mechanism for the considered system is of great importance and for some ranges of quantum dot molecule parameters is the dominant contribution to relaxation. It is shown that the phonon-assisted tunneling is much faster (down to ∼ 6 ps even at zero temperature) in comparison with other decoherence processes. The influence of Coulomb interaction is discussed and its consequences are indicated. We calculate the relaxation rates for GaAs quantum dot molecules and study the dependence on quantum dot size, distance and offset between the constituent quantum dots. In addition the temperature dependence of the tunneling rates is analyzed.
Keywords: tet_topic_qd

Zahlungsbereitschaften für Geschäftsmodelle produktbegleitender Dienstleistungen --- Wirtschaftlichkeit bei der Vermarktung hybrider Produkte - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Weddeling, Matthias (Technologie und Dienstleistung: Innovationen in Forschung, Wissenschaft und Unternehmen Beiträge der 7. Dienstleistungstagung des BMBF)

Ordnungsrahmen für die hybride Wertschöpfung - Becker, J; Beverungen, Daniel; Knackstedt, R; Glauner, C; Stypmann, M; Rosenkranz, C; Schmitt, R; Hatfield, S; Schmitz, G; Eberhardt, S; Dietz, M; Thomas, O; et al. (Dienstleistungsmodellierung --- Methoden, Werkzeuge und Branchenlösungen)

Wertschöpfungsnetzwerke von Produzenten und Dienstleistern als Option zur Organisation der Erstellung hybrider Leistungsbündel - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Wertschöpfungsnetzwerke --- Konzepte für das Netzwerkmanagement und Potenziale aktueller Informationstechnologien)